RESTARTING MICE EVENTS AFTER COVID-19: A LOOK AT READINESS, CHALLENGES AND STRATEGIES TO RESTART (Journal of Event, Tourism and Hospitality Studies, 2024)
The novel coronavirus disease (COVID-19) outbreak from March 2020 until 2021 brought great losses to all business sectors including the MICE industry. Therefore, it is imperative to conduct a stringent analysis on the need to restart MICE events, as it is part of the adaptability, recovery, and resilience of the events industry. For this reason, the content of webinars streamed live on open-access platforms such as YouTube as well as event companies’ websites or their Facebook pages between Jan 2021 and October 2021 were reviewed and analysed. The speakers and panellists of the selected webinars are experts in event management. The majority of them are established industry practitioners and key people in their respective organisations. As the main decision-makers of their companies, their thoughts and perceptions are valid and relevant as they can determine their companies’ policy. By exploring their individual experiences and roles in handling COVID-19, a holistic understanding of crisis management can be obtained. The results of the content analysis suggest three main themes to be considered before restarting MICE events such as readiness, challenges and strategies to restart the MICE business. This knowledge would greatly assist the companies in restarting their business operation during a crisis.